Environmental law - Bell, Stuart McGillivray, Donald Pedersen, Ole W. Lees, Emma (Oxford University Press, 2017)
Approached thematically to help students plot a memorable map of the issues, the ninth edition of this established text provides far-reaching, lucid coverage of the fundamentals and enriching learning features to develop critical thinking and high-level understanding.